ANALISIS FAKTOR YANG BERPENGARUH TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2009 - 2013 - Noviana Aristyawati P, 11.05.52.0155; Puspitasari, Elen (Students Journal of Accounting and Banking, 2015)
This study aims to transform and analyze the effect of profitability, the composition of the board of directors, audit committee number, company size, fiscal loss compensation and leverage against tax avoidance in the mining company listed on the Indonesia Stock Exchange period 2009 - 2013. In this study, researchers used population of all financial data mining company listed on the Stock Exchange during the years 2009-2013. The method used is purposive sampling method. The samples used were 16 mining companies listed on the Stock Exchange during the years 2009-2013 in a row. Test equipment in this study using multiple linear regression, partial test (t test) and a simultaneous test off (f test). Results of this research is the positive effect on the profitability of tax avoidance, independent commissioner has no effect on tax avoidance, the number of audit committee has no effect on tax avoidance, the size of the company a positive effect on tax avoidance, tax loss carryforwards no effect on tax avoidance, and leverage no effect on tax avoidance.Keywords: Profitability, The Composition of The Board of Directors, Audit Committee Number, Company Size, Fiscal Loss Compensation, Leverage, Tax Avoidance